2011
DOI: 10.1002/ajh.22009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and clinical outcomes of cataracts following hematopoietic stem cell transplantation

Abstract: To evaluate the characteristics of cataracts following hematopoietic stem cell transplantation (HSCT), 561 patients without any ocular complications before HSCT were reviewed. Ocular complications occurred in 196 patients (34.9%). Cataract was diagnosed in 45 of 561 patients. The 10-year estimated cataract incidence was 14%. The median onset time was 498 days after transplant (range, 38-4,535 days). The onset of cataracts was later than that of other ocular complications. Phacoemulsification was performed in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…In addition to TBI, prolonged steroid therapy, such as for treatment of GVHD, has been identified as an independent risk factor for cataracts after HCT. 13,14 A population-based study showed that even inhaled corticosteroids were associated with the development of posterior subcapsular and nuclear cataracts. 15 Survivors of allogeneic HCT are more likely to develop cataracts, when compared with those of autologous HCT.…”
Section: Cataractsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to TBI, prolonged steroid therapy, such as for treatment of GVHD, has been identified as an independent risk factor for cataracts after HCT. 13,14 A population-based study showed that even inhaled corticosteroids were associated with the development of posterior subcapsular and nuclear cataracts. 15 Survivors of allogeneic HCT are more likely to develop cataracts, when compared with those of autologous HCT.…”
Section: Cataractsmentioning
confidence: 99%
“…The most commonly reported ocular toxicity of anti-cancer drugs is keratoconjunctivitis. Systemic corticosteroids accelerate cataract formation 13,14,85 and glaucoma development. 66 Topical corticosteroids are commonly used for treatment of ocular GVHD, but their long-term use is associated with elevated intraocular pressure, decreased epithelial healing, infection and cataracts.…”
Section: Medications With Ocular Toxicitiesmentioning
confidence: 99%
“…Along with TBI, prolonged steroid therapy, such as for treatment of GVHD, has been identified as an independent risk factor for cataracts after HCT [13,14]. A population-based study showed that the use of even inhaled corticosteroids was associated with the development of posterior subcapsular and nuclear cataracts [15].…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…The most commonly reported ocular toxicity of anti-cancer drugs is keratoconjunctivitis. Systemic corticosteroids accelerate cataract formation [13,14,85] and glaucoma development [66]. Topical corticosteroids are commonly used for treatment of ocular GVHD, but their long-term use is associated with elevated intraocular pressure, decreased epithelial healing, infection, and cataracts [18].…”
Section: Medications With Ocular Toxicitiesmentioning
confidence: 99%
“…Als weitere okuläre Komplikationen nach allogener HSCT entwickeln bis zu 85 % der Patienten eine (meist subkapsuläre) Katarakt, die rasch progredient sein kann und durch die Steroidtherapie und ggf. auch Radiatio bedingt ist [22,23]. Seltener kommt es im Verlauf zu einer steroidinduzierten okulären Hypertension.…”
unclassified